ANALYSIS OF THE ADVENTIVE FRACTION OF THE FLOODWATER OF THE DNIPR RIVER IN THE BOUNDARIES OF THE NORTHERN STEPPE - Karmyzova Ліна (Biota. Human. Technology, 2024)
The aims of the study. Provide a list and conduct an analysis of the adventitious fraction of the flora of vascular plants of the floodplain of the Dnipro River within the Northern Steppe. Methodology. Research was carried out using general botanical methods of collection, herbarium, and species identification. When studying the flora of reservoirs, special hydrobotanical methods were used. The species names of the studied flora are given according to Mosyakin & Fedoronchuk (1999). The analysis of the adventitious fraction was carried out according to the time of deposition - archaeophytes, neophytes and the degree of naturalization - spontaneous, naturalized (Richardson, 2000). The analysis is based on the Kornás classification (Kornás, 1968). Scientific novelty. For the first time, a list of adventive species of vascular plants of the floodplain of the Dnipro River within the Northern Steppe is provided. Its analysis was carried out according to the time of introduction and the degree of naturalization. Conclusions. As a result of the research, it was established that the adventitious flora of vascular plants of the Dnipro River floodplain within the Northern Steppe is characterized by a significant number of adventives - 175 species, compared to the adventive flora of the Northern Steppe Prydniprovya - 357 species (Baranovski et al., 2023). This indicates a significant anthropogenic and climatic influence on the vegetation cover of this region. According to the time of introduction of the allochthonous element to the studied territory, it is divided into two groups: archaeophytes - 94 species (35.7%) and neophytes - 169 species (64.3%). According to the degree of naturalization, the species are distributed as follows: naturalized archaeophytes - 73 species (27.8%), naturalized neophytes - 75 species (28.5%), spontaneous archaeophytes - 21 species (8.%), spontaneous neophytes - 94 species (35 .7%). Among the represented flora of the adventitious fraction, the primary range of most species is Mediterranean - 73 species (27.8%), Asian - 55 species (21%) and North American - 52 species (19.8%). Other species have the following primary range: European – 24 species (9.1%), Irano-Turanian – 17 species (6.5%), Mediterranean-Irano-Turanian – 16 species (6%), range of unknown origin – 7 species (2.7%), South American - 7 species (2.7%) and the area of anthropogenic origin - 3 species (1.1%).